Public health education: A report from Mosul and a plan for change - Golden Kathie; Mack Ally; Hughes Gail D (BMC, 2005)
Abstract Background Today Iraq suffers from severe shortages of food, medicine, clean water and adequate sanitation. Malnutrition and communicable diseases are major factors in the rising morbidity and mortality rates. However, supplies and equipment are insufficient or outmoded, and public health training is outdated. The Universities have been unable to help because under-funding and isolation from their professional colleagues has limited their effectiveness. Methods To revitalize public health education, we describe a partnership between a US education consortium and the University of Mosul that will be carried out in the next several years. The plan is based on "three R's": Recovery from the past damage due to war and neglect; Retooling of key public health faculty to remedy the years of isolation and restriction of activity; and Reestablishment of the University as a resource for the its constituents, for the community and for other educational institutions. In all these activities, Iraqi minorities, especially women, will participate and contribute. Conclusion The work to repair the public health educational infrastructure has just begun. When completed, it will represent a small but necessary step in restoring normalcy to the people of Mosul, and of Iraq.